Perceptual difference of smile aesthetics between 2-dimensional photographs and 3-dimensional dentofacial images: a cross-sectional study - Zhuoxing Xiao; Gui Chen; Yijiao Zhao; Yong Wang; Yan Gu (BMC Oral Health, 2023)
Abstract Background The aim of this study was to compare the perceptual difference of smile aesthetics between 2D photographs and 3D dentofacial images as perceived by orthodontists and graduate students. Methods Forty-eight subjects finished orthodontic treatment were recruited with 2D photographs of frontal, oblique and lateral views as well as 3D dentofacial images. Twelve senior orthodontists and 13 postgraduate students were asked to rate the 2D and 3D smile simulations based on visual analog scale (VAS) and to vote for smile features that affect the attractiveness of smile. At the end, they completed a questionnaire about their views on different smile simulations. Wilcoxon signed-rank, Bland–Altman analysis, and multiple linear regression were used to compare the ratings and votes of smile perception between raters and between records. Results Orthodontists and postgraduate students rated smile consistently with 2D photographs, while orthodontists tended to give a higher rate for unattractive smiles and a lower rate for attractive smiles with 3D dentofacial images. The 3D dentofacial images were rated significantly lower than 2D photographs and the voting of most of the smile features showed significant negative main effect on VAS scores, while the effect of demographic characteristics of raters, voting on visible width of upper dentition and buccal corridor was not significant. In addition, a significant negative main effect of commissure and facial profile was found on the rating discrepancy between 2D and 3D images. Conclusions Senior orthodontists tend to perceived 3D images more conservatively in smile evaluation. 3D dentofacial images were rated lower than 2D photographs and most of the smile features affect the aesthetic perception of smile. The perceptual difference of commissure and facial profile contributed to the lower ratings in 3D dentofacial images.